Philosophy-in-Action in University Teaching - Scott, Sue M.; Chovanec, Donna M.; Young, Beth (Canadian Journal of Higher Education, 1994)
Fourteen professors expressed their "traditional," "humanist," and "critical" philosophies about teaching and learning when they engaged in dialogue with us and each other. The relationship between their philosophy of teaching and their practice in the classroom is the research question. Four themes that elaborate these philosophies-in-action emerged from a grounded-theory approach to data analysis. One theme, "Expert vs. Co-learner" describes these professors' views of themselves as teachers. A second theme, "The Relationship of Comfort to Critique, " outlines some of the tensions that arise from attempting to create a comfortable classroom environment while also encouraging critical thought. "Learning for Change, " the third theme, is about the differing forms of change in the learner that these professors seek as evidence that learning is taking place. Finally, in the section called "Coping with Constraints, " our study participants identify institutional issues that have made it difficult for them to enact their particular teaching-learning philosophies in university classes.